Enhancement of anisotropic thermoelectric performance of tungsten disulfide by titanium doping. Issue 26 (15th June 2016) - Huang, Zhiwei; Wu, Tianmin; Kong, Shuang; Meng, Qing-Long; Zhuang, Wei; Jiang, Peng; Bao, Xinhe
Abstract : Using a facile doping strategy, the thermoelectric performance of tungsten disulfide is enhanced up to 70 times. Our study will stimulate further exploration of the potential applications in thermoelectrics for transition metal dichalcogenide semiconductors and other two-dimensional materials. Abstract : Thermoelectric power generators, as one promising renewable energy resource, have attracted intense attention over the past few decades. However, the large-scale use of thermoelectric convertors relies on cost-effective and eco-friendly thermoelectric materials with decent efficiency. For transition metal dichalcogenide semiconductors (TMDCs), a potential thermoelectric material, their thermoelectric efficiency is hampered by their poor intrinsic electrical conductivities. Herein, we demonstrate that the thermoelectric performance of WS2, a typical TMDC material, can be dramatically enhanced by up to 70 times by doping with titanium. The anisotropic thermoelectric properties of these layered WS2 structures were also systematically revealed. The realization of decent thermoelectric efficiency of WS2 by a facile doping strategy will stimulate future explorations of thermoelectric applications for other TMDCs and layered materials.